The aegis of Zeus, symbol of the warrior value of the god - Lucena, Alcione (Romanitas - Revista de Estudos Grecolatinos, 2016)
The shield is the weapon that, in warrior induement, most expressively represents the hero’s excellence. Being Zeus the first hero, and considering his warrior formation process and his role as general of the war between Greeks and Trojans, we look forward to prove in this article, by the identification of warring character of episodes in which the aegis, the god’s shield, takes part, the presence of the warring strength of Zeus. This strength is determinant to the establishment of the Cosmos, which occurred through war, as well.